Optimizing CCR Platforming Conditions for Platformate Quality - Hersa Rizki Rahkmatullah; Martomo Setyawan; Siti Jamilatun (Talenta Publisher, 2025)
The CCR Platforming unit converts hydrotreated naphtha into platformate as a high-octane gasoline blending component. This study evaluates the effects of reactor temperature and catalyst circulation rate on platformate quality, represented by Research Octane Number (RON), and coke tendency, represented by carbon spent. Operating and laboratory data from reactor section 14-R-601/602/603 were grouped at average temperatures of 510, 515, and 520°C with catalyst rates of 60% and 65%. The variables were processed using average data analysis, graphical interpretation, multiple linear regression, and validation against laboratory RON with a maximum allowable error of 5%. The condition of 520°C at 60% catalyst rate produced the best platformate quality, with average RON of 100.00, but carbon spent was relatively high at 6.207 wt%. Increasing the catalyst rate to 65% at 510°C improved the frequency of RON ≥ 100; however, at 515 and 520°C the RON did not increase significantly because higher feed flow increased reaction load and coke formation. Model validation gave a MAPE of 0.481% and maximum error of 1.751%. These results indicate that CCR Platforming optimization requires balancing RON target, feed load, catalyst circulation, coke formation, and regeneration effectiveness.